Levels of anxiety and depression related to COVID-19 among physicians: An online cross-sectional study from Turkey - Kurt, Osman; Deveci, Suleyman Erhan; Oguzoncul, Ayse Ferdane (Bayrakol Medical Publisher, 2020)
Aim: In this study, we aimed to determine anxiety and depression levels related to COVID-19 infection of assistant physicians who were taking medical specialty training in a medical faculty hospital. Material and Methods: We performed this cross-sectional study in a medical faculty hospital located in Turkey's Eastern Anatolia region. The universe of the survey was composed of all assistant physicians (342 persons) who were taking medical specialty training in this hospital. We aimed to reach the entire universe without selecting a sample. Of the physicians, 264 have been accessed (responsiveness rate 77.2%). In combination with sociodemographic questions, State-Trait Anxiety Inventory Test (STAI) and the Beck Depression Inventory (BDI) were used. STAI measured state anxiety value, whereas BDI depression findings. Results: Women accounted for 51.9% of the study participants and the mean age of those was 29.7 +/- 3.5. Of the physicians, 81.1% thought that the COVID-19 infection influenced themselves spiritually and 84.1% of participants were afraid of getting an infection because of being a healthcare worker, while 98.5% of transmitting the infection to their relatives or environment. The anxiety and depression scores of women were determined to be significantly higher than the scores of men. We found a significant difference between anxiety and depression and regret about choosing a medical profession, thoughts of leaving the assistantship. Discussion: Anxiety and depression levels of female physicians were significantly higher than male physicians. In our study, a large proportion of physicians (84.1%) were found to be afraid of getting infected with COVID-19 and transmitting the infection to any of their relatives (98.5%). In this study, no significant relationship was established between marital status and anxiety and depression levels.
Keywords: COVID-19; Depression; Anxiety; Physician